2018
DOI: 10.1515/jpem-2017-0363
|View full text |Cite
|
Sign up to set email alerts
|

Adult height in patients with familial male-limited precocious puberty and the role of an aromatase inhibitor in patient management

Abstract: Aromatase inhibitor therapy is associated with a positive height outcome in FMPP but the outcome with and without intervention is unpredictable. Clinicians need to be cautious when counselling families about the potential height outcome in FMPP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 40 publications
0
16
0
2
Order By: Relevance
“…Most recent studies have shown good outcomes with anti-androgens such as bicalutamide and third generation aromatase inhibitors such as anastrozole ( 4 , 6 , 7 , 8 ). These treatments, in conjunction with one another, have shown better adult height potential preservation than either alone ( 5 ). In one study, anti-androgens alone did not prevent early growth plate closure ( 5 ), and in another, anastrozole was ineffective in treating continued aggressiveness ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Most recent studies have shown good outcomes with anti-androgens such as bicalutamide and third generation aromatase inhibitors such as anastrozole ( 4 , 6 , 7 , 8 ). These treatments, in conjunction with one another, have shown better adult height potential preservation than either alone ( 5 ). In one study, anti-androgens alone did not prevent early growth plate closure ( 5 ), and in another, anastrozole was ineffective in treating continued aggressiveness ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…These treatments, in conjunction with one another, have shown better adult height potential preservation than either alone ( 5 ). In one study, anti-androgens alone did not prevent early growth plate closure ( 5 ), and in another, anastrozole was ineffective in treating continued aggressiveness ( 7 ). Bicalutamide and anastrozole offer the additional advantage of a prolonged half-life that allows for convenient once-daily dosing while other anti-androgen agents would require multiple daily doses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations